Factors Influencing National Quality Indicator Reporting Compliance at Independent Medical and Dental Practices - Yayang Putri Yudhistirha; Misnaniarti Misnaniarti; Alvera Noviyani (Newinera Publisher, 2026)
The National Quality Indicators (NQI) are instruments used to measure and evaluate the quality of healthcare services at health facilities, including Independent Medical and Dental Practices (IMDPs). Compliance with NQI reporting is an important component in monitoring and improving healthcare quality; however, its implementation still faces various challenges. This study aims to analyze the factors influencing compliance with National Quality Indicator reporting at Independent Medical and Dental Practices. This study employed a Systematic Literature Review (SLR) method guided by the PRISMA framework. Literature searches were conducted through Google Scholar, PubMed, ScienceDirect, Scopus, and Garuda for articles published between 2021 and 2025. Articles were selected based on predetermined inclusion and exclusion criteria and subsequently analyzed using a narrative synthesis approach. The review findings indicate that NQI reporting compliance is influenced by individual, organizational, and support system factors. Individual factors include the knowledge, understanding of quality indicators, competence, and motivation of healthcare workers. Organizational factors encompass management support, quality culture, supervision, audits, and feedback. Support system factors include workload, resource availability, and the utilization of information technology and health information systems. Knowledge and understanding of quality indicators were identified as the most dominant factors in improving reporting compliance. NQI reporting compliance at Independent Medical and Dental Practices is influenced by various interrelated factors. Improving reporting compliance requires strengthening the competencies of healthcare workers, optimizing health information systems, organizational support, and continuous monitoring and evaluation to support the improvement of healthcare service quality.